Extraplaque versus intraplaque tracking in chronic total occlusion percutaneous coronary intervention. Issue 6 (28th September 2022) - Megaly, Michael; Buda, Kevin; Karacsonyi, Judit; Kostantinis, Spyridon; Simsek, Bahadir; Basir, Mir B.; Mashayekhi, Kambis; Rinfret, Stephane; McEntegart, Margaret; Yamane, Masahisa; Azzalini, Lorenzo; Alaswad, Khaldoon; et al.
Abstract: Objective: To compare the clinical outcomes after extraplaque (EP) versus intraplaque (IP) tracking in chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Background: The impact of modern dissection and reentry (DR) techniques on the long‐term outcomes of CTO PCI remains controversial. Methods: We performed a systematic review and meta‐analysis of studies that compared EP versus IP tracking in CTO PCI. Odds ratios (ORs) with 95% confidence intervals (CIs) are calculated using the Der‐Simonian and Laird random‐effects method. Results: Our meta‐analysis included seven observational studies with 2982 patients. Patients who underwent EP tracking had significantly more complex CTOs with higher J‐CTO score, longer lesion length, and more severe calcification and had significantly longer stented segments. During a median follow‐up of 12 months (range 9–12 months), EP tracking was associated with a higher risk of major adverse cardiovascular events (MACE) (OR 1.50, 95% CI (1.10–2.06), p = 0.01) and target vessel revascularization (TVR) (OR 1.69, 95% CI (1.15–2.48), p = 0.01) compared with IP tracking. There was no difference in the incidence of all‐cause death (OR 1.37, 95% CI (0.67–2.78), p = 0.39), myocardial infarction (MI) (OR 1.48, 95% CI (0.82–2.69), p = 0.20), stent thrombosis (OR 2.09, 95% CI (0.69–6.33), p = 0.19), or cardiac death (OR 1.10, 95% CI (0.39–3.15), p = 0.85) between IP and EP tracking. Conclusion: EP tracking is utilized in more complex CTOs and requires more stents. EP tracking is associated with a higher risk of MACE, driven by a higher risk of TVR at 1 year, but without an increased risk of death or MI compared with IP tracking. EP tracking is critically important for contemporary CTO PCI.